Análise e modelagem de vibrações auto-excitadas no processo de torneamento de ligas de titânio por elementos finitosa - Degan, Bruno Zambrano (Universidade Federal de São Carlos, 2023)
A critical parameter in machining processes is the final surface quality of the machined part, directly related to self-excited vibrations that arise in these processes due to the interaction between the cutting tool and the surface, thus impairing the final roughness obtained and intensifying the wear of the machining tool. cut. Thus, it becomes interesting to model these vibrations to obtain ideal ranges of cutting parameters, especially machining depth and rotation, ensuring better productivity without jeopardizing the surface quality of the machined parts. In the present work it is proposed, through the finite element method, the modeling of the self-excited vibrations in the turning process of titanium alloys, aiming at the creation of stability lobe diagrams through frequency response functions and machining constants, in order to evaluate the degree of influence of superior vibration modes on the stability diagrams and to allow an integration between the finite element model and a model for calculating the stability of the processes.
Analysis and modeling of self-excited vibrations in the finite element turning process of titanium alloys
Keywords: Diagramas de lóbulos de estabilidade; Vibrações auto-excitadas; Elementos finitos; Torneamento; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO